UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA DENGAN MENGGUNAKAN METODE REKA CERITA GAMBAR - Sri Hartati (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2018)
Learning student speaking skills is an important part of teaching Indonesian. Through learning speaking skills students are expected to be able to: Dialogue with other people, Express messages, opinions, experiences and feelings logically and systematically, discussing with regard to procedures and manners, submitting reports, speeches, remarks or lectures. and verbal feelings have been learned and possessed by students before they enter school. This ability is obtained by students in the family environment and other environments outside the school environment. But the talent that this student has is not enough to make students skilled in speaking in front of the class. The purpose of this study was to improve the speaking skills of class X.4 students of SMA Negeri 1 Trimurjo. The results of this study are the skills of the students of SMA N 1 Trimrjo in speaking with their stories when the picture can be improved. This can be proven from the results that reached an average value of 55.75 after being given action I increased to 64.88 and after being given action II to 70.38 Keywords— Reka Method Picture Story, Speaking Skills, Trimurjo Senior High School 1